1992
DOI: 10.1111/j.1600-0609.1992.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone marrow cellularity by magnetic resonance imaging in patients with myelodysplastic syndrome

Abstract: Magnetic resonance imaging (MRI) is a safe modality for examining the bone marrow and it is quite effective in revealing marrow involvement in hematological malignancies. MRI has been compared with needle marrow biopsy in 22 patients with myelodysplastic disorders. A fairly good concordance has been demonstrated in 79% of cases. However, in 5 patients MRI revealed that bone marrow hyperplasia was not generalized. Therefore in elderly patients with MDS, MRI of the spine allows the quantification of bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…55 Although the BM blast percentage, cytogenetics, and mutational analysis would also not be available, these limitations could eventually be overcome by obtaining PB genetic information, 56,57 by flow cytometry, 58 and also by medical imaging. 59,60 A recent study has demonstrated that specific morphologies may be associated with somatic mutations. 61 Perhaps, conversely, specific genetic signatures reflect corresponding morphologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…55 Although the BM blast percentage, cytogenetics, and mutational analysis would also not be available, these limitations could eventually be overcome by obtaining PB genetic information, 56,57 by flow cytometry, 58 and also by medical imaging. 59,60 A recent study has demonstrated that specific morphologies may be associated with somatic mutations. 61 Perhaps, conversely, specific genetic signatures reflect corresponding morphologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…MRI of bone marrow in patients with aplastic anaemia (AA) or myelodysplastic syndrome (MDS) has been reported previously (9)(10)(11)(12)(13). In this study, we examined the signal intensity (SI) patterns on STIR images in patients with AA and MDS (14), and describe follow-up STIR images during the course of those patients treated with recombinant human granulocyte colony stimulating factor (rhG-CSF), recombinant human erythropoietin (rhEPO) or other agents.…”
Section: Introductionmentioning
confidence: 99%
“…The subjective interpretation of BMC, despite the reported high interobserver agreement,33,34 as well as the changes in quality of the specimens and the focal nature of BM findings, may have limited the accuracy of BMC determination. This limitation will hopefully be addressed by accurate future technologies, such as MRI38 and 18F-PET 39. The translated qualitative BMC information to quantitative values (ie, 30%, 60%, 90%) is somewhat arbitrary, yet it is likely that these numbers, on average, signify a close proximity to the actual BMC.…”
mentioning
confidence: 99%